Regulation of the Immune Response by the Aryl Hydrocarbon Receptor - Gutiérrez-Vázquez, Cristina; Quintana, Francisco J (Immunity (Cambridge, Mass.), 2018)
The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that is activated by small molecules provided by the diet, microorganisms, metabolism, and pollutants. AhR is expressed by a number of immune cells, and thus AhR signaling provides a molecular pathway that integrates the effects of the environment and metabolism on the immune response. Studies have shown that AhR signaling plays important roles in the immune system in health and disease. As its activity is regulated by small molecules, AhR also constitutes a potential target for therapeutic immunomodulation. In this review we discuss the role of AhR in the regulation of the immune response in the context of autoimmunity, infection, and cancer, as well as the potential opportunities and challenges of developing AhR-targeted therapeutics.